Better late than never: sleep still supports memory consolidation after prolonged periods of wakefulness - Petzka, M; Zika, O; Staresina, BP; Cairney, SA (Cold Spring Harbor Laboratory Press, 2023)
While the benefits of sleep for associative memory are well established, it is unclear whether single-item memories profit from overnight consolidation to the same extent. We addressed this question in a preregistered, online study and also investigated how the temporal proximity between learning and sleep influences overnight retention. Sleep relative to wakefulness improved retention of item and associative memories to similar extents irrespective of whether sleep occurred soon after learning or following a prolonged waking interval. Our findings highlight the far-reaching influences of sleep on memory that can arise even after substantial periods of wakefulness.